Navigating HIV-Related Stigma in Switzerland: A Qualitative Study - Gilles, Ingrid; Jackson-Perry, David; Le Saux, Clara; Storari, Chiara; Cart-Richter, Ellen; Keserue Pittet, Oriana; Darling, Katharine E. A. (International Journal of Public Health, 2024)
Objectives. This study sought to understand how people living with HIV experience, perceive, and navigate stigma in their everyday life and in care settings in an urban French-speaking area in Switzerland. Methods. Semi-structured interviews were carried out with 19 people living with HIV in Lausanne concerning their experience of HIV-related stigma in both everyday life and in healthcare settings. Content analysis was performed to identify main and sub-themes. Results. ‘Living with HIV’ posed little or no difficulty for participants. However, the burden of anticipated and internalized HIV-related stigma played a disproportionately large role in their lives. Participants considered the general population’s low level of knowledge about HIV as problematic in this regard. While participants reported few examples of enacted stigma generally, healthcare environments were sometimes experienced as sites of prejudice and discrimination. However, some healthcare professionals were also sources of information and knowledge, contributing to participants’ ‘journeys of self-acceptance’. Conclusions. Even in an urban environment in a country with ready access to healthcare and education, HIV-related stigma remains a concern for people living with HIV.